Analysis of the canting stability as a factor determining the lateral wear of rails - E. A. Sidorova; R. M. Kurtikov (Вестник Научно-исследовательского института железнодорожного транспорта)
Reducing the intensity of rail lateral wear remains an important task for industry science. As part of solving this problem, studies are being carried out on the influence of the geometry of the rail track on the wear of rails, the intensity of the force interaction of wheels and rails, the tribological characteristics of the contacting surfaces. The article focuses on the influence on the wear of the geometry of the rail track, namely the rail canting. The definition of the stability of the rail canting has been formulated, which makes it possible to proceed to the assessment of this indicator both in time and in the length of the track section. The assessment of the canting stability over time was carried out on the basis of experimental data obtained in the course of field studies carried out in 2019–2020 on the Moscow Railway. As a result of evaluating these data, the dependence of the change in the average values and the standard deviation of the rail canting in the section on time was built. The average values and standard deviation of the canting in the investigated area are considered in this article as a set of parameters that make it possible to assess the canting stability. In addition to these parameters, it is proposed to evaluate the canting stability along the length of the section based on the canting offset and the standard deviation. The assessment of the stability of the rail canting along the length of the section was carried out using calculations performed in the “Universal Mechanism” software package. As a result of calculations, the values of frame and lateral forces were obtained and an assessment of their maximum and average values at the site was made. This made it possible to answer the question: how does the retraction of the rail canting affect the level of force interaction at the point of contact between the wheels and rails, and, hence, the wear rate?